LEAD Removal from Industrial Wastewater by Electrocoagulation process - K. Shakir, Ibtehal; I. Husein, Besma (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
This investigation was carried out to study the treatment and recycling of wastewater in the Battery industry for an effluent containing lead ion. The reuse of such effluent can only be made possible by appropriate treatment method such as electro coagulation. The electrochemical process, which uses a cell comprised aluminum electrode as anode and stainless steel electrode as cathode was applied to simulated wastewater containing lead ion in concentration 30 – 120 mg/l, at different operational conditions such as current density 0.4-1.2 mA/cm2, pH 6 -10 , and time 10 - 180 minute. The results showed that the best operating conditions for complete lead removal (100%) at maximum concentration 120 mg/l was found to be 1.2 mA/cm2 current density, in alkaline media pH = 10 , and at 120 minute.